Management of specialists’ professional training in university college: theoretical aspect - Братко, Марія Василівна (ScienceRise: Pedagogical Education, 2016)
There were studied theoretical grounds of the management of specialists’ training in conditions of the higher educational institution on the principles of environmental approach. There was actualized an essence of basic notions of environmental approach, components (personal, information-content, organizational-activity, spatial-substantive) and parts of polystructural educational function (educational-professional, educational-socializing, educational-cultural) of educational environment of the higher educational institution. On the base of analysis of educational environment phenomenon of the higher educational institution, modern approaches to the management of educational organizations there was made a conclusion, that due to its phenomenal features educational environment of the higher educational institution is the one of main factors of personal formation in the process of higher education. Environmental approach in education changes accents in pedagogical activity: the direct teacher’s influence on person is replaced by activity, directed on creation and development of environment that must satisfy educational needs of education recipient in the optimal order. It was established, that environmental approach due to its essential properties provides indirect (trough the projecting of educational environment) management of personal formation in the process of professional education, guaranteeing the conditions for gaining professional competence, general cultural and personal development